Policies and unthought of regional integration of Cape Verde in ECOWAS - (:unkn) unknown (My University, 2024)
The specificities of the Cape Verdean archipelago in the West African regional context are regularly mobilized in public discourse to justify the complexity of the process. The cultural societal framework and historical creolization are presented as the original causes of Cape Verdean singularity in West Africa. However, the retrospective analysis of trade and circulation in the region provides access to certain keys to understanding necessary for the interpretation of today's regional state relations. Certainly, geography, the « ethnic » unity of the nation, etc., make the construction of the Cape Verdean state an exception within the community. However, is this enough to explain the relations between Cape Verde and ECOWAS? According to Cape Verdean analysts and national practitioners, the country's foreign policy is described as pragmatic. The community approach is described as a strategy that would make it possible to combine different institutional anchors, while maintaining a certain independence. While it is true that in theory it is indeed possible to be a member of the CPLP, to have a (special) partnership with the European Union, the UN, or the United States… In practice, what are the concrete consequences of the superposition of these commitments, in particular, in terms of: security, mobility, trade. In terms of defense, how to position oneself in the event of conflicts? At the borders, what rules should be applied? For trade, what standards should be favored? Conversely, is Cape Verdean specificity taken into consideration during the process of developing ECOWAS regional policies (in accordance with the initial text)? By approaching regional integration from the organizational model of its administration and the operational functioning of its institutions and by going back to the colonial origins of the European Union, we can shed light on the origins of ECOWAS's institutional mimicry towards the EU. Thus, by analyzing the legal instru
Keywords: African Research